(untitled) (Research, Society and Development, 2022)
Energy, presented in various forms, is of fundamental importance to the development of mankind, and its correct understanding for the potential with subsequent conversion to assist in work activities has always been a challenge and motivation for the brightest minds. Therefore, it is essential to investigate ways to improve the efficiency in the use of energy resources, especially exergetic analysis, which has been applied since the 1970s, in order to find more rational use of energy, and, at the same time, reduce the consumption of fossil fuels and transforming the application of energy efficiency. In this context, the present paper aims to perform a literature review on exergy in refrigerators. It was verified that the objective of the work was met, since it was presented 9 studies that verified the energy efficiency through exergy in refrigerators. It was found that there are few studies in the Brazilian literature, presenting itself as a lack.